2017
DOI: 10.1080/00223980.2017.1314929
|View full text |Cite
|
Sign up to set email alerts
|

Learning Disabilities and Emotional Intelligence

Abstract: The literature is conflicted around the subject of the emotional abilities of individuals with Specific Learning Disabilities (SLDs): While many claim cognitive challenges are associated with emotional difficulties, some suggest emotional and interpersonal abilities are not compromised in such disorders and may help individuals compensate and cope effectively with the challenges they meet in learning environments. Two studies explored differences in emotional intelligence (EI) between young adults with and wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 47 publications
2
8
0
2
Order By: Relevance
“…Regarding the published literature on self-concept and its possible association with EI in primary school students [46] and in secondary school students [47,48], there are several studies examining the significant differences in EI abilities related to self-concept. Nevertheless, there are very few studies on university students with disabilities [49]. The study of EI in these people can be important when it comes to promoting, in them, adequate control and management of their emotional state.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the published literature on self-concept and its possible association with EI in primary school students [46] and in secondary school students [47,48], there are several studies examining the significant differences in EI abilities related to self-concept. Nevertheless, there are very few studies on university students with disabilities [49]. The study of EI in these people can be important when it comes to promoting, in them, adequate control and management of their emotional state.…”
Section: Introductionmentioning
confidence: 99%
“…To date, only Zysberg and Kassler[ 27 ] have measured the EI abilities in individuals with SpLD. They have reported that adult SpLD college students (mean age 25.77 yrs., SD 3.11) have similar overall EI abilities as their regular peers.…”
Section: Discussionmentioning
confidence: 99%
“…Data kualitatif hasil wawancara individual dengan keenam partisipan dan pengasuh utama mereka dianalisis secara tematik. Analisis tematik kualitatif merupakan metode identifikasi, analisis, dan pelaporan pola atau tema dalam data (Braun & Clarke, 2006 Identifikasi emosi yang lebih lamban dan kurang efektif merupakan kecenderungan yang ditemukan pada anak-anak dengan kesulitan belajar spesifik (Elias dalam Zysberg & Kasler, 2017). Meskipun demikian, orang tua juga berkontribusi dalam pendidikan emosi anak (emotion coaching; Gottman, Katz, & Hooven, 1996).…”
Section: Desain Penelitianunclassified